TO THE ISSUE OF EXTENDING THE SERVICE LIFE OF CARS FOR TRANSPORTATION OF PELLETS - Anofriev, V. H.; Reidemeister, O. H.; Kalashnyk, V. A.; Kulieshov, V. P. (Science and Transport Progress, 2016)
Purpose. Freight rolling stock of «Ukrzaliznytsia» primarily has cars that are overaged. The same situation is observed in the park of specialized cars. So the car fleet for the transport of pellets consists of about 50% of cars that served one-and-a-half and more lifetimes. However, the volume of shipments of iron ore is constant for a number of years. In this regard, there is a need to find methods to justify continuing useful life of cars and to assess the conformity of residual life of the car body structure to operating load for an extended period of use. Methodology. When selecting the cars for the test their condition underwent technical diagnosis in order to identify the level of corrosion and mechanical damage. The next stages of the tests included the experimental determination of the loading level and the stress state of car body carcass based on strength and endurance tests and the evaluation of the possible values of the extended period of operation. Findings. Pre-test diagnosing of cars showed that the technical condition of cars for transportation of pellets, as a whole, is in satisfactory condition. Carried out static and impact strength tests with subsequent evaluation of strength of the car structural elements showed that the strength of the latter is provided in accordance with regulations and such cars do not threaten the traffic safety. Shock endurance tests have shown that all the cars have passed endurance tests with no damage that would impede testing and could not be removed during scheduled repairs. The cars had lifelength that allows prolong their useful life after one-and-a-half lifetime. Originality. The work presents the estimate of the residual life of bodies of pellet transportation cars, which spent one-and-a-half of the set lifetime. Practical value. The experimental results confirm the possibility of extending the service life of cars after one-and-a-half life of their lifetime. The results of the work can be used to extend the service life of cars for transportation of pellets. Part of the rolling stock, which had to be written off in connection with the expiration of the set one-and-a-half lifetime without additional measures can continue its lifetime.